Effect of silver inhibition on the ceramic foam as flame suppression - Hamzah Nur Faazila; Kasmani Rafiziana Md.; Chandren Sheela (E3S Web of Conferences, 2024)
Aluminium dust explosions pose significant safety and economic challenges in various industrial processes. Due to this, the current research explores an innovative approach by inhibiting the silver nanoparticles (Ag NPs) to ceramic porous form substrate as a flame suppressant in order to mitigate the risks associated with these explosions. The antimicrobial and non-toxic qualities of silver are also attractive to be applied in medical and food technology. However, the interfacial adhesion between the metallic (nanosilver) and non-metallic (silica-based-ceramic) is still vaguely studied due to the mechanical and surface energy mismatch between the organic surface and the inorganic layers. From this study, the physicochemical and mechanical properties of the silver-coated ceramic foam were analyzed using X-ray diffraction, field emission scanning electron microscopy with energy dispersive X-ray, thermogravimetric analysis, and compression test. From the mechanical testing, it was found that the percentage increase of maximum load for silver-ceramic foam from the original ceramic foam was about 60%. The results indicate that silver-coated foam has a better compressive strength of 0.93 MPa as compared to 0.58 MPa by the original ceramic. The inhibition effect of Ag NPs powder on the explosion pressure evolution and flame spread mechanism of aluminium powder at different concentrations and particle sizes was tested using the Hartmann experimental system.